DUAL CAREER COUPLE: EXPLICIT CHALLENGES FOR WORK-LIFE COMBINATION - Prof Rekha Mahajan (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Changes in the idea of careers, and furthermore of families, mean new difficulties for the expanding number of double career bcouples in the public arena. Each couple faces numerous worries, including two individual professions, a divided relationship and the association between these elements. The point of this paper is to give a far reaching diagram of the subject of DCCs; discuss the expected preferences and hindrances of this association plan; and survey discoveries on DCCs in the zone of pressure and prosperity; career and portability issues; association and parenthood issues; just as sexual orientation related questions, strategies for encouraging the work-life joining of DCCs on the individual level, fair and square of couples, and fair and square of associations.